A Rare Complication of an Ingested Foreign Body: Gallbladder Perforation - Safak Karacay; Koray Topçu; Selami Sözübir (Case Reports in Gastrointestinal Medicine)
We present a 13-year-old child who admitted with a dull right upper quadrant pain that started 3 weeks before her referral. Several medications were given but they did not change the intensity and the frequency of the pain. Her physical examination was nonspecific except for slight right upper quadrant tenderness. The imaging studies revealed a sewing pin perforating the stomach and gallbladder. The patient was treated with a successful operation, and no postoperative complications were observed. To our knowledge, this is the first case of a sharp foreign body gallbladder perforation in a child.